2003
DOI: 10.1007/s00468-002-0216-0
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange and chlorophyll fluorescence responses of Pinus radiata D. Don seedlings during and after several storage regimes and their effects on post-planting survival

Abstract: Post-storage gas exchange parameters like CO 2 assimilation, stomatal conductance, transpiration, water use efficiency and intercellular CO 2 concentrations, together with several chlorophyll a fluorescence parameterswere examined in radiata pine (Pinus radiata D. Don) seedlings that were stored for 1, 8 or 15 days at 4°or 10°C with or without soil around the roots. Results were analysed in relation to post-storage water potential and electrolyte leakage in order to forecast their vitality (root growth potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
3
7
0
1
Order By: Relevance
“…Carbon assimilation and dry mass accumulation. One important reason for better quality of seedlings stored in light mainly the result of the preservation of the photosynthetic ability (Kubota and Kozai, 1994;Mena-Petite et al, 2003), which would ensure the transplant quality of post-storage seedlings effectively (Hou et al, 2010;Sato et al, 2004). As shown in Figure 4, plants stored in light showed a marked high value in Pn accompanied by higher g S , Ci, and Tr than in darkness after 8 d of storage, which is in agreement with the changes in F v /F m and FPSII.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Carbon assimilation and dry mass accumulation. One important reason for better quality of seedlings stored in light mainly the result of the preservation of the photosynthetic ability (Kubota and Kozai, 1994;Mena-Petite et al, 2003), which would ensure the transplant quality of post-storage seedlings effectively (Hou et al, 2010;Sato et al, 2004). As shown in Figure 4, plants stored in light showed a marked high value in Pn accompanied by higher g S , Ci, and Tr than in darkness after 8 d of storage, which is in agreement with the changes in F v /F m and FPSII.…”
Section: Resultssupporting
confidence: 72%
“…Kubota and Kozai (1994) found that broccoli plantlets stored in light could preserve their photosynthetic ability. Similar results were also observed in seedlings of Phalaenopsis (Su et al, 2001) and radiata pine (Mena-Petite et al, 2003). Compared with storage, the recovery of post-storage photosynthetic performance is very crucial for plants (Hou et al, 2010;Sato et al, 2004).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…As mentioned, the reasons for the higher photosynthesis in grafted watermelon seedlings might be: 1) a higher carbohydrate reserve in the leaves of grafted seedlings contributed to photosynthesis; and 2) higher activities of antioxidant enzymes in the grafted seedlings scavenged the excess ROS, reduced the chlorophyll loss, and protected the photosynthetic system during storage. In addition, our previous study showed that the grafted ones had a stronger root system and quicker root regeneration after transplanting compared with the non-grafted watermelon seedlings (Ding et al, 2009), which could supply enough water to maintain a high photosynthetic rate (Mena-Petite et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A determinação da fl uorescência da clorofi la a por ser uma técnica rápida, precisa e não destrutiva, tem sido usada para investigar danos causados por vários tipos de estresses sobre o aparato fotossintético (Oliveira et al 2002;Mielke et al 2003;Gonçalves et al 2005;Fernández 2006;Lavinsky et al 2007;Naumann et al 2008). Além disso, os parâmetros de fl uorescência da clorofi la a também têm se mostrado como ferramenta sensível capaz de diagnosticar a redução da assimilação de CO 2 e/ou destruição da estrutura fotossintética (Mena-Petite et al 2003). Sendo o fotossistema II responsável pelo fornecimento de energia para a fotossíntese, a avaliação de sua efi ciência mediante medidas da emissão da fl uorescência da clorofi la a pode ser usada como indicador dos danos causados pelo alagamento em espécies arbóreas.…”
Section: Introductionunclassified